Students’ Perception on Offline-Online Learning in Speaking Class of English Education Study Program in Universitas Negeri Padang - Siti Aisyah Indah Sumanika; Nora Fudhla (Universitas Negeri Padang, 2023)
Speaking is one of the challenging skills for students to master because they must use the skill whenever they interact in an English setting. Speaking has always been regarded as one of the most essential skill to master in the history of English language teaching and learning. The aimed of this research was to investigate the advantages and disadvantages of online – offline learning in speaking for formal interaction class of English Education Study Program in Universitas Negeri Padang and to describe what the students think of offline and online learning (students’ engagement). This research employed a descriptive qualitative study. The respondents of this research were 85 students which were Class 3, 4 and 5 at third semester English Education Study Program in UNP who become the sample of this research. This study used open and closed-ended questionnaire. This research found that there were 5 advantages of offline and 5 advantages of online learning then also there were 4 disadvantages of offline and 5 disadvantages of online learning based on the students’ preference. Mostly the students have good engagement while learning speaking in offline rather than in online class. The students have big eager to participate speaking class in offline learning rather than online. They said that in offline class, they always actively participate, whether responding to the lecturer's questions or making presentations in class. Mostly the students answered it was easy or not too difficult to complete the task while studying speaking in offline learning. And also the students feel excitement and challenging while studying speaking in offline class rather than online.